GASTRONOMIC TOURISM IN LIMA METROPOLITAN: SUPPLY AND DEMAND DIAGNOSIS - Carreño Farfán, David (2015)
This research project focuses on the Gastronomic Tourism of Lima. It is located within so-called “Historical Center” through the identification of Food&Beverage companies constituting the existingsupply against tourist behavior and requirements. It aims to develop a situational analysis and to propose alternatives for their development and greater satisfaction of both parties. The work is proposed to be a study that can guide other surveys related to this subject and studies in other geographic areas, as the trend of the gastronomic industry in Peru issustain ably growing. It also aims to provide a contribution to help develop this type of tourism giving knowledge to the private sector as well as the Peruvian Society of Gastronomy and local government through Councils and responsible sectors for the area.